Effect of sensor specific body location on wireless network routing performance - Habaebi, Mohamed Hadi; Abduljali, E.; Ragaibi, T.; Rhuma, N. (Institution of Engineering and Technology, 2008)
The effect of locating wireless sensors on a monitored patient’s body on the performance of routing protocols is studied. Results indicate a considerable difference in sensor node forwarding activity, power consumption, and routing load as a function of sensor height. The Results motivate exploiting this criteria to develop new energy-efﬁcient routing strategies.